Interleukin-10 contributes to reservoir establishment and persistence in SIV-infected macaques treated with antiretroviral therapy - Justin Harper; Susan P. Ribeiro; Chi Ngai Chan; Malika Aid; Claire Deleage; Luca Micci; Maria Pino; Barbara Cervasi; Gopalan Raghunathan; Eric Rimmer; Gulesi Ayanoglu; Guoxin Wu; et al. (The Journal of Clinical Investigation, 2022)
Interleukin-10 (IL-10) is an immunosuppressive cytokine that signals through STAT3 to regulate T follicular helper (Tfh) cell differentiation and germinal center formation. In SIV-infected macaques, levels of IL-10 in plasma and lymph nodes (LNs) were induced by infection and not normalized with antiretroviral therapy (ART). During chronic infection, plasma IL-10 and transcriptomic signatures of IL-10 signaling were correlated with the cell-associated SIV-DNA content within LN CD4+ memory subsets, including Tfh cells, and predicted the frequency of CD4+ Tfh cells and their cell-associated SIV-DNA content during ART, respectively. In ART-treated rhesus macaques, cells harboring SIV-DNA by DNAscope were preferentially found in the LN B cell follicle in proximity to IL-10. Finally, we demonstrated that the in vivo neutralization of soluble IL-10 in ART-treated, SIV-infected macaques reduced B cell follicle maintenance and, by extension, LN memory CD4+ T cells, including Tfh cells and those expressing PD-1 and CTLA-4. Thus, these data support a role for IL-10 in maintaining a pool of target cells in lymphoid tissue that serve as a niche for viral persistence. Targeting IL-10 signaling to impair CD4+ T cell survival and improve antiviral immune responses may represent a novel approach to limit viral persistence in ART-suppressed people living with HIV.